EDUKASI WORK-LIFE INTEGRATION MELALUI OPTIMALISASI RESOURCES DAN STRATEGI PENGELOLAAN TUNTUTAN KERJA PADA WANITA KARIR - Novena Maria Vianney; Zamralita Zamralita; Urip Purwono (COMMUNITY : Jurnal Pengabdian Kepada Masyarakat, 2026)
ABSTRACT The increasing flexibility and digitalization of work have intensified the challenge of integrating professional and personal responsibilities, particularly for career women who often face overlapping work and family demands. Inadequate management of these demands may negatively affect psychological well-being, productivity, and overall quality of life. This community service program aimed to enhance participants’ understanding of work-life integration, psychological resources, and adaptive strategies for managing multiple roles through an educational webinar entitled “Beyond Balance: The Art of Managing Work Demands and Resources to Achieve Work-Life Integration among Career Women.” The activity was conducted online via Zoom in collaboration with Kite Creative and involved 41 participants from diverse professional backgrounds. The program was implemented through three main stages: delivery of educational materials, interactive discussion and reflection sessions, and evaluation using pre-test, post-test, and participant feedback forms. The topics covered included work-life integration, job demands, job resources, psychological capital, and practical coping strategies. Evaluation results indicated a substantial increase in participants’ average understanding scores, rising from 73% in the pre-test to 98% in the post-test. Participants also reported positive perceptions regarding the relevance of the materials, speaker performance, and overall implementation of the webinar. These findings suggest that research-based educational webinars can effectively improve psychological literacy and strengthen adaptive capacities among career women in managing work and personal life demands. ABSTRAK Perubahan pola kerja yang semakin fleksibel dan terdigitalisasi menghadirkan tantangan bagi pekerja dalam mengelola tuntutan pekerjaan dan kehidupan personal. Tantangan ini lebih kompleks bagi wanita karir karena harus menjalankan berbagai peran profesional, keluarga, dan sosial secara bersamaan. Ketidakmampuan mengintegrasikan berbagai peran tersebut berpotensi menurunkan kesejahteraan psikologis, produktivitas, dan kualitas hidup. Kegiatan Pengabdian kepada Masyarakat (PKM) ini bertujuan meningkatkan pemahaman peserta mengenai pengelolaan tuntutan kerja, pemanfaatan sumber daya psikologis, dan strategi mencapai work-life integration melalui webinar edukatif bertajuk “Beyond Balance: Seni Mengelola Tuntutan Kerja dan Sumber Daya untuk Mencapai Work-Life Integration pada Wanita Karir.” Kegiatan dilaksanakan secara daring bekerja sama dengan Kite Creative dan diikuti oleh 41 peserta dari berbagai latar belakang profesi. Metode pelaksanaan meliputi penyampaian materi, diskusi interaktif, refleksi peserta, serta evaluasi melalui pre-test, post-test, dan umpan balik peserta. Materi mencakup konsep work-life integration, job demands, job resources, psychological capital, dan strategi adaptif dalam mengelola berbagai peran kehidupan. Hasil evaluasi menunjukkan peningkatan rata-rata skor pemahaman peserta dari 73% pada pre-test menjadi 98% pada post-test. Mayoritas peserta juga memberikan penilaian positif terhadap materi dan pelaksanaan kegiatan. Temuan ini menunjukkan bahwa webinar edukatif efektif meningkatkan literasi psikologis dan kemampuan adaptif wanita karir dalam mewujudkan work-life integration.